Istanbul's Modernization- Period Hotels (1840-1914) - Yakartepe, Elif Celebi; Binan, Can (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2011)
The modernization period in the 19th century caused important changes in systems of both travel and accommodation systems. These changes inevitably affected the architecture of hotels and other buildings offering accommodation. The first modern hotels were opened in Galata and Pera by the date of 1840. (It means first hotel opened in 1840 and then the other hotels began to open) Later hotels began to serve tje in Eminonu, Kadikoy, Bogazici, Adalar, Sisli, Ferikoy and Yesilkoy regions. The opening and development of hotels has continued until the beginning of the First World War in 1914. There were hotels with suit rooms and some communal space and there were also hotels which were as luxurious and wellequipped as European hotels. First hotels were traditionally built of wood or stone, and had only two or three floors. At the end of the century, hotels were modern structures built using modern materials such as brick and steel, larger and higher than their predecessors. Beside that these hotels did not have typical facades, they were constructed with traditional, neoclassical or mixed facades. The grand luxury hotels were designed by famous European architects and craftsmen and often magnificently decorated. These grand hotels are also important because of the technical equipment and technology at the date they were built. Because of being very important point for many in the domain of science, modernization period hotels of Istanbul's are studied by many aspects as urbanisme, architecture, preservation, tourism and sustainability. In addition, the hotels are evaluated in terms of commerce and managerment conception, socio-economic status and political importance. And then it is defined deformations and their causes of these hotels. Finally suggestions are made that would remove these deformations. It is believed the data included in this work will be helpfull for planning, arranging and conservation works in Istanbul.
Keywords: Istanbul; hotel; accomodition; conservation; architecture